End winding mount integrated motor drive - Abebe, Robert (2018)
With increased need for high power density, high efficiency and high temperature capabilities in Aerospace and Automotive applications, Integrated Motor Drives (IMD) offer a potential solution. . A number of IMD configurations already exist, each with their respective merits, drawbacks and industrial applications. Despite these potential benefits of IMDs, thermo-mechanical concerns remain over the close coupling integration of the power module and machine